2007
DOI: 10.1532/hsf98.20061175
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Significance of Plasma Levels of Interleukin-6 and High-Sensitivity C-Reactive Protein in Atrial Fibrillation after Coronary Artery Bypass Surgery

Abstract: Elevated IL-6 and hsCRP levels in patients with postoperative AF suggest inflammatory components have a role of in the pathogenesis of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 32 publications
1
46
2
1
Order By: Relevance
“…Thus, VCAM-1 allows identifying a high-risk population which exhibit an increased level of baseline inflammation associated with endothelial activation, rendering them more susceptible to the inflammatory injury associated to CPB. Baseline hsCRP levels in our cohort was higher than previously described in other groups [15,25], which can be explained by the high-risk profile of our patients. This increased baseline inflammatory state may explain the lack of association in our cohort between pre-operative hsCRP levels and POAF, and may also be a reason for the absence of significant difference in plasma ICAM-1 levels, evidencing the limitations in the interpretation of general inflammatory markers in moderate-to-high-risk populations [46].…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Thus, VCAM-1 allows identifying a high-risk population which exhibit an increased level of baseline inflammation associated with endothelial activation, rendering them more susceptible to the inflammatory injury associated to CPB. Baseline hsCRP levels in our cohort was higher than previously described in other groups [15,25], which can be explained by the high-risk profile of our patients. This increased baseline inflammatory state may explain the lack of association in our cohort between pre-operative hsCRP levels and POAF, and may also be a reason for the absence of significant difference in plasma ICAM-1 levels, evidencing the limitations in the interpretation of general inflammatory markers in moderate-to-high-risk populations [46].…”
Section: Discussioncontrasting
confidence: 76%
“…When baseline markers for inflammation and oxidative stress were compared, no significant differences were observed between patients with and without POAF. Baseline inflammatory markers were higher than those previously reported by others [15,25] and they increased significantly after surgery both in patients with or without POAF ( Fig. 1 and Table 2).…”
Section: Baseline Laboratory Tests Echocardiographic and Clinical Datamentioning
confidence: 38%
See 2 more Smart Citations
“…After cardiac surgery the presence of a relationship between AF development and interleukin 8 (IL-8), IL-6 and increased WBC count has been shown (15)(16)(17). In a very recent study, Rienstra et al (18) examined the 936 participants in the Framingham Heart Study original cohort and found that an increased WBC count was associated with AF incident during 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%